Mortality, sarcopenic obesity, and sarcopenia: Frailty in Brazilian Older People Study – FIBRA – RJ - Campos, Glaucia Cristina de; Lourenço, Roberto Alves; Molina, Maria del Carmen Bisi (Revista de Saúde Pública, 2021)
OBJECTIVE: To investigate the risk of mortality associated with sarcopenic obesity (SO), obesity (OB), and sarcopenia in elderlies. METHODS: We analyzed longitudinal data from 270 participants > 65 years of age of Phase III of the Study on Frailty in Brazilian Older People (FIBRA–RJ–2012). Socioeconomic, demographic, lifestyle, morbidity, and functional data were collected by home based interviews. DXA and body composition assessment was conducted in a laboratory. In women, OB was diagnosed when body fat percentage ≥ 38% and sarcopenia by an Appendicular Lean Mass Index (ALMI) < 6.00 kg/m² and muscle strength < 16 Kgf. In men, OB was diagnosed when body fat percentage ≥ 27%, and sarcopenia was diagnosed with ALMI < 7.00 kg/m² and muscle strength < 27 Kgf. SO was assessed by combining variables used to diagnose obesity and sarcopenia. The probabilistic linkage method was used to obtain deaths in the 2012-January 2017 period from the Brazilian Mortality Registry. Cox regression models were tested, and crude and adjusted hazard ratio calculations were conducted. RESULTS: After adjusting for sex, age, race/skin color, walking as an exercise, and hypertension, individuals with sarcopenia were 5.7 times more likely to die (95%CI: 1.17–27.99) than others without sarcopenia and obesity. CONCLUSION: A high risk of death was observed in individuals with sarcopenia. These results show the need for preventive strategies of early detection and treatment in order to increase survival employing multimodal interventions.